Telocytes in pancreas of the Chinese giant salamander (Andrias davidianus). Issue 11 (20th September 2016) - Zhang, Hui; Yu, Pengcheng; Zhong, Shengwei; Ge, Tingting; Peng, Shasha; Guo, Xiaoquan; Zhou, Zuohong
Abstract: Telocytes (TCs), novel interstitial cells, have been identified in various organs of many mammals. However, information about TCs of lower animals remains rare. Herein, pancreatic TCs of the Chinese giant salamanders ( Andrias davidianus ) were identified by CD34 immunohistochemistry (IHC) and transmission electron microscopy (TEM). The IHC micrographs revealed CD34 + TCs with long telopodes (Tps) that were located in the interstitium of the pancreas. CD34 + TCs/Tps were frequently observed between exocrine acinar cells and were close to blood vessels. The TEM micrographs also showed the existence of TCs in the interstitium of the pancreas. TCs had distinctive ultrastructural features, such as one to three very long and thin Tps with podoms and podomers, caveolae, dichotomous branching, neighbouring exosomes and vesicles. The Tps and exosomes were found in close proximity to exocrine acinar cells and α cells. It is suggested that TCs may play a role in the regeneration of acinar cells and α cells. In conclusion, our results demonstrated the presence of TCs in the pancreas of the Chinese giant salamander. This finding will assist us in a better understanding of TCs functions in the amphibian pancreas.